Matching-up celebrities' brands with products and social causes. Issue 2 (11th March 2019) - Santos, Ana Luisa; Barros, Filipa; Azevedo, António
Abstract : Purpose: Beyond traditional brand endorsement, many celebrities have in recent years decided to launch their own product lines, which may be used to promote their own celebrity brand. Which product categories or social causes match a celebrity's brand personality? This study aims to investigate the antecedents of celebrity–product degree of fit and willingness to pay (WTP)/make a donation in different scenarios. The manipulation of the scenarios aims to capture the role of celebrity attributes, perceived personality profiles, product involvement and acceptance of social causes. Design/methodology/approach: In total, 335 respondents answered an online questionnaire with a factorial plan corresponding to 20 different matching scenarios: five celebrities/perceived personalities (Emma Watson, Jennifer Lawrence, Kim Kardashian, Natalie Portman and Scarlet Johansson) × four types of branding scenarios (a lipstick for low involvement; a watch for high involvement; an eco-foundation for "high social acceptance" and vodka for "low social acceptance/controversial"). Findings: Scarlett Johansson obtained the highest degree of fit, both for launching her own brand of lipstick or a watch. Kim Kardashian had the best degree of fit for launching her own vodka brand, while Emma Watson's attributes confirmed that she would be seen as the ideal founder of an eco-foundation. Significant predictors of WTP/make a donation were assessed by multiple linear regression for each type of product. Practical implications: The paper provides recommendations that may help guide celebrity brand managers through the celebrity–product matching process. Social implications: Celebrity branding in relation to social causes is also discussed in this paper. Originality/value: This study explores a gap found in the literature as it explores the product match-up hypotheses within a celebrity branding context and moreover extends this investigation to social causes and products with different degrees of involvement and social acceptance.